Simultaneous Sinus Lifting and Alveolar Distraction of a Severely Atrophic Posterior Maxilla for Oral Rehabilitation with Dental Implants - Kanno, Takahiro (Hindawi Publishing Corporation, 2012)
We retrospectively reviewed a new preimplantation regenerative augmentation technique for a severely atrophic posterior maxilla using sinus lifting with simultaneous alveolar distraction, together with long-term oral rehabilitation with implants. We also analyzed the regenerated bone histomorphologically. This study included 25 maxillary sinus sites in 17 patients. The technique consisted of alveolar osteotomy combined with simultaneous sinus lifting. After sufficient sinus lifting, a track-type vertical alveolar distractor was placed. Following a latent period, patient self-distraction was started. After the required augmentation was achieved, the distractor was left in place to allow consolidation. The distractor was then removed, and osseointegrated implants (average of 3.2 implants per sinus site, 80 implants) were placed. Bone for histomorphometric analysis was sampled from six patients and compared with samples collected after sinus lifting alone as controls (n = 4). A sufficient alveolus was regenerated, and all patients achieved stable oral rehabilitation. The implant survival rate was 96.3% (77/80) after an average postloading followup of 47.5 months. Good bone regeneration was observed in a morphological study, with no significant difference in the rate of bone formation compared with control samples. This new regenerative technique could be a useful option for a severely atrophic maxilla requiring implant rehabilitation.